Risk measures and the cost of equity in the new economy biotechnology industry. (4th August 2014) - Sadorsky, Perry; Henriques, Irene
The cost of equity is important in valuing new investment opportunities and in evaluating the ongoing performance of existing business projects. This is especially true in the new economy biotechnology industry. The purpose of this paper is to calculate the cost of equity for the Canadian biotechnology industry using several different risk measures. The risk measures include systematic risk, total risk, downside risk, and value at risk. The results are useful for managers, budget planners, investors, policy makers, and others who are interested in the financing and risk management of new economy firms.